2016
DOI: 10.3389/fnhum.2016.00576
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lumbar Muscle Fatigue on Trunk Adaptations during Sudden External Perturbations

Abstract: Introduction: When the spine is subjected to perturbations, neuromuscular responses such as reflex muscle contractions contribute to the overall balance control and spinal stabilization mechanisms. These responses are influenced by muscle fatigue, which has been shown to trigger changes in muscle recruitment patterns. Neuromuscular adaptations, e.g., attenuation of reflex activation and/or postural oscillations following repeated unexpected external perturbations, have also been described. However, the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
2
15
2
1
Order By: Relevance
“…The reaction times in the present study are markedly longer than what has previously been reported [ 15 , 16 , 17 , 23 , 24 ]: Abboud [ 17 ] performed a similar experiment where participants experienced a sudden load increase of the trunk and found a mean reaction time of 94 ms, while the pooled mean reaction time (left and right side pooled) in the present study is 115 ms. Abboud et al [ 17 ] asked their participants to perform an active contraction of the trunk flexor muscles of 10% MVC. The difference in results between their and our study could be partially due to the active contraction priming the sensory system to be more alert, and therefore more ready for the perturbation resulting in shorter reaction times.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The reaction times in the present study are markedly longer than what has previously been reported [ 15 , 16 , 17 , 23 , 24 ]: Abboud [ 17 ] performed a similar experiment where participants experienced a sudden load increase of the trunk and found a mean reaction time of 94 ms, while the pooled mean reaction time (left and right side pooled) in the present study is 115 ms. Abboud et al [ 17 ] asked their participants to perform an active contraction of the trunk flexor muscles of 10% MVC. The difference in results between their and our study could be partially due to the active contraction priming the sensory system to be more alert, and therefore more ready for the perturbation resulting in shorter reaction times.…”
Section: Discussioncontrasting
confidence: 54%
“…Reaction time was defined as the time from the magnet release to the onset of muscle activity in the m. erector spinae. This was done in accordance with procedures used in previous work investigating reaction time [ 15 , 16 , 17 ]. We defined the limit for onset of muscle activity to 5% of maxEMG.…”
Section: Methodsmentioning
confidence: 99%
“…This scale is calculated quickly, and it is convenient and easy for test-takers to understand. Its validity and reliability have also been widely reported for evaluating fatigue [20,21].…”
Section: Personal Perception Of Fatiguementioning
confidence: 97%
“…High-density surface electromyography (HDsEMG) has been increasingly used to study how pain (Falla et al, 2017), fatigue (Abboud et al, 2016), and repetitive task execution (Samani et al, 2017) alter the spatial distribution of EMG amplitude. Changes in the spatial distribution of EMG amplitude reflect a variety of physiological (mal) adaptations.…”
Section: Introductionmentioning
confidence: 99%